Youthfulness, inexperience, and sleep loss: the problems young drivers face and those they pose for us - Groeger, J A (BMJ Group, 2006)
Young inexperienced drivers are more likely to be involved in road traffic crashes than drivers who are older and more experienced. This paper argues that neither age nor inexperience are, in and of themselves, sufficient explanations of the association between age, experience, and casualty rates. The aim here is to consider what it is about inexperienced young drivers in particular that may increase crash risk. Evidence is reviewed showing differential sleep loss among different teenage groups, which may relate to recently presented evidence that young teenagers are more crash involved than drivers in their early twenties. Potential acute and chronic effects of sleep loss among teenagers and young adults are described.